PENGARUH TINGKAT PENGANGGURAN TERBUKA TERHADAP TINGKAT KEMISKINAN : STUDI EKONOMI REGIONAL PROVINSI KEPULAUAN BANGKA BELITUNG - Donesia, Dora; -, Abdurrahman; Idzuka, Vinka; Okarina, Sherren; Tri Rizkidianto, Muhammad Sadiq; Rizki Putra, Agung (JSE: Jurnal Sharia Economica, 2025)
This study aims to determine the effect of the open unemployment rate on the poverty rate in the Province of Bangka Belitung Islands. Unemployment and poverty are crucial and interrelated issues that affect each other and influence regional economic development. The data used in this study is secondary data obtained from the relevant agency, namely the Central Bureau of Statistics (BPS) of Bangka Belitung Province, covering the period from 2002 to 2024. The data analysis method employed is a simple linear regression model using SPSS 30 software. The results of this study show that the open unemployment rate variable has a positive and significant effect on the poverty rate in Bangka Belitung Province. The higher the unemployment rate, the higher the poverty rate.